2017
DOI: 10.1080/23746149.2017.1346483
|View full text |Cite
|
Sign up to set email alerts
|

Growth of crystalline phase change materials by physical deposition methods

Abstract: Phase change materials are a technologically important mate rials class and are used for data storage in rewritable DVDs and in phase change random access memory. Furthermore, new applications for phase change materials are emerging. Phase change materials with a high structural quality, such as offered by epitaxial films, are needed in order to study the fundamental properties of phase change materials and to improve our understanding of this materials class. Here, we review the progress made in the growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…The samples on the Si(111)-7 × 7 reconstruction additionally feature rotational domains. An XRD peak indicating the formation of vacancy layers is observed attributing the epitaxial films to the metastable vacancy-ordered phase [24,28].…”
Section: Sample Preparation and Stm/sts Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples on the Si(111)-7 × 7 reconstruction additionally feature rotational domains. An XRD peak indicating the formation of vacancy layers is observed attributing the epitaxial films to the metastable vacancy-ordered phase [24,28].…”
Section: Sample Preparation and Stm/sts Experimentsmentioning
confidence: 99%
“…These layers are partly stacked in a regular sequence, as deduced from XRD and TEM [24]. This more ordered phase deviates from the rocksalt structure and has recently been dubbed the metastable vacancy-ordered phase [28]. Moreover, it is known that the epitaxial films are strongly p-type doped [35] with an unintentionally varying charge carrier density p = (0.1-3) × 10 26 m −3 [24,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epitaxial growth of PCMs has established a new level of material quality 810 and thus allows for an improved determination of their properties using techniques that normally cannot be applied to polycrystalline samples. For example, the electronic band structure of PCMs has been studied by angle-resolved photoemission spectroscopy 11,12 , which is not possible using polycrystalline samples.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, superlattices have also been fabricated in a single crystal form using molecular beam epitaxy (MBE) [21][22][23][24] and pulsed laser deposition (PLD) 25 and comprehensive transmission electron microscopy (TEM) experiments were carried out on such samples. [26][27][28][29][30][31] These measurements demonstrated that the (as-grown) structures were different from the original intuitive models proposed for the iPCM SET and RESET states.…”
mentioning
confidence: 99%